Análisis de las variables antropométricas y físico técnicas en voleibol femenino - Valladares Iglesias, N.; Joao, P. V.; Garcia-Tormo, J. V. (Revista Ciencia del Deporte, 2016)
Volleyball has been considered a highly complex sport because of their technical, tactical, physical, psychological and anthropometric factors requirements. Over the years there has been an increase in the homogeneity of the characteristics of volleyball players in high performance due to talent acquisition with similar skills. The main interest of this study was to determine the performance of a sample of 53 volleyball players participating in different official women's volleyball competition. The variables studied are: category, anthropometric variables (body mass, height, endomorphy, mesomorphy, ectomorphy), upper body strength (throwing ball, measure the speed hitting without jump and with jump spike) and lower body strength (CMJ, ABK, DJ and jump spike). Statistical analysis consisted of a Shapiro-Wilks test, to determine the normality of the sample. The comparative analysis between categories was performed using an analysis of variance (ANOVA) a factor. The results showed a significant positive increase in physical, technical and anthropometric characteristics of the players with the increased level of competition, and a better use of technical gestures, reflecting an increase in performance thereof.